EFFECT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURES ON MARKET VALUE OF LISTED CONSUMER GOODS COMPANIES IN NIGERIA (Journal of Global Accounting, 2025)
The study investigated how environmental, social, and governance (ESG) disclosures affect the market value of consumer goods companies in Nigeria. The variables of ESG disclosures were regressed on the market value (tobins’q). Purposive sampling technique was used to select 13 consumer goods companies out of the study’s population of 21 companies. Secondary data was extracted from selected 13 annual reports of quoted consumer goods companies from 2013 to 2022. The study applied descriptive statistics and panel data estimation regression. The findings showed that governance disclosure had a favorable and substantial impact on the market value (Tobin's Q) of listed consumer goods companies, while environmental and social disclosure had an inverse but substantial effect on market value. Hence, the study concluded that ESG substantially influences the market value of listed consumer products businesses in Nigeria. According to the study, companies should include ESG disclosure in their annual reports because it has a long-term impact on market value and should integrate it into their long-term strategic objectives for sustainable growth..
Keywords: Consumer Goods Companies; Environmental; Social, and Governance; Market value; Tobins’Q